Psychological Recovery through Art Therapy for Earthquake Victims in Jorong Timbo Ateh Kecamatan Talamau Pasaman Barat - Hardi, Emeliya; Jumiarti, Desri; Ardimen, Ardimen; Masril, Masril (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The earthquake in West Pasaman occurred very strongly and was accompanied by other disasters such as landslides and floods (galodo). Natural disasters are one of the causes of anxiety and other negative emotions in victims, they can even cause trauma which greatly affects the psychology of victims, especially children. The purpose of this service activity is for the psychological recovery of post-earthquake children by using art therapy by drawing, coloring, playing, and singing to children who are in the Jurong Timbo Abu Ateh evacuation post, Talamau District, West Pasaman Regency. The children looked happy, and there was a decrease in their anxiety levels.